Microbiota intestinal y ácidos grasos de cadena corta en pacientes críticos (2016)
ABSTRACT: Different studies have shown changes in gut microbiota and short-chain fatty acids in critically ill patients with Systemic Inflammatory Response Syndrome (SIRS). Aim: To review the evidence about the role of gut microbiota and SCFAs in critically patients and its modulation with prebiotics, probiotics and symbiotic. Materials and Methods: A search of the literature in Pubmed, Science Direct, Ovid, Medline and Scopus databases was conducted. The terms used were microbiota, critically ill, intensive care unit, systemic inflammatory response syndrome, short-chain fatty acids, prebiotics, probiotics and symbiotic. Results: The intestinal microbiota in critically ill patients is reduced in number and diversity, which can lead to dysregulation of the systemic immune response to the pathogenic invasion. Changes in SCFAs in critically ill patients are attributed to a decrease of obligate anaerobic bacteria and the fermentation substrates required for its production. The gut microbiota modulation with prebiotics, probiotics and symbiotic suggest improvement in bowel function. Conclusions: Gut microbiota and SCFAs are altered in critically ill patients; therefore, maintaining the intestinal environment is key for reducing complications and improving prognosis.